Advancing the human rights of children with communication needs in school. (2nd January 2018) - Gallagher, Aoife L.; Tancredi, Haley; Graham, Linda J.
Abstract: Article 19 of the Universal Declaration of Human Rights states that everyone has the right to freedom of opinion and expression. However, due to difficulties in communicating, children with speech, language and communication needs (SLCN) are at particular risk of not being heard. Although it is recommended that children with SLCN can and should be actively involved as equal partners in decision-making about their communication needs, speech–language pathologists (SLPs) can lose sight of the importance of supporting communication as a tool for the child to shape and influence choices available to them in their lives. Building these skills is particularly important for SLPs working in mainstream educational contexts. In this commentary, the authors argue the need for a shift in emphasis in current practice to a rights-based approach and for SLPs to take more of an active role in supporting children with SLCN to develop agency and be heard. We also present some concepts and frameworks that might guide SLPs to work in a right-based way in schools with this population.